Nasal Analysis and Anatomy: Anthropometric Proportional Assessment in Asians—Aesthetic Balance from Forehead to Chin, Part II - Park, JinSoo (Semin Plast Surg, 2015)
Caucasians usually have reduction or correction rhinoplasty; however, Asian nasal surgery is mainly for augmentation rhinoplasty. Therefore, an Asian rhinoplasty should start with a precise understanding of ethnic anatomical differences. The authors summarize the anatomical characteristics of Asians to ensure the best results.